Pengaruh Strategi Penjualan, Kualitas Pelayanan Terhadap Kepuasan Pelanggan : (Studi Pada Pelanggan Apotek Kimia Farma Kota Bima) - Nur Khusnul Hamidah; Hanifah Muthiah (Public Service and Governance Journal, 2024)
A pharmacy is a place that carries out pharmaceutical activities which has an important role in obtaining information about drugs. In this case, pharmacists have the responsibility to create customer satisfaction. Customer satisfaction is the key to the success of a business. Different services will also have a very significant impact on a pharmacy. Apart from that, the company must also market its products by implementing the right sales strategy, because by implementing the right strategy the company will get the expected results. This research aims to determine the sales strategy, service quality and customer satisfaction at Kimia Farma Pharmacy, Bima City, which is located on Jl. Soekarno Hatta Paruga.